2020
DOI: 10.1111/jfpe.13487
|View full text |Cite
|
Sign up to set email alerts
|

Drying kinetics behavior of turkey breast meat in different drying methods

Abstract: In this study, turkey breast meat samples were dried with hot air (60, 75, 90 C), microwave (180, 360, 540 W) and freeze (0.1, 0.15, 0.2 mbar) drying and parameters related to the drying kinetics of turkey breast meat were investigated. Although a constant drying rate was not observed for all drying methods, the drying process occurred only during the falling drying rate period. Microwave drying process times were lower than those of hot air and freeze drying because of volumetric heating. Drying times decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…From these studies, it appears that during the drying of beef slices, all the drying occurs in the falling rate drying period. This is in agreement with other studies where other muscle-based matrices have been used, such as chicken (Başlar et al, 2014), restructured chicken jerky (Luckose et al, 2017), sliced turkey breast (Elmas et al, 2020), raw and cooked chicken (Hii et al, 2014), and salmon and trout (Başlar et al, 2015). Conversely, Aksoy et al ( 2019) observed a constant rate period during the VD and the USV of minced beef, which is in agreement with the results of the study of Sa-adchom et al (2011a) on drying kinetics of pork slices using superheated steam.…”
Section: Drying Curves: Drying-time and Drying-rate Curvessupporting
confidence: 89%
See 1 more Smart Citation
“…From these studies, it appears that during the drying of beef slices, all the drying occurs in the falling rate drying period. This is in agreement with other studies where other muscle-based matrices have been used, such as chicken (Başlar et al, 2014), restructured chicken jerky (Luckose et al, 2017), sliced turkey breast (Elmas et al, 2020), raw and cooked chicken (Hii et al, 2014), and salmon and trout (Başlar et al, 2015). Conversely, Aksoy et al ( 2019) observed a constant rate period during the VD and the USV of minced beef, which is in agreement with the results of the study of Sa-adchom et al (2011a) on drying kinetics of pork slices using superheated steam.…”
Section: Drying Curves: Drying-time and Drying-rate Curvessupporting
confidence: 89%
“…This phenomenon takes places when the outer surface of a material dries out much faster that the core, resulting in the formation of a dry, hard, and impermeable crust that prevents moisture from the core getting to the meat surface to be evaporated (Gulati & Datta, 2015). Elmas et al (2020), who dried turkey breast meat slices with hot air (60, 75, and 90 • C), microwave (180, 360, and 540 W), and freeze (0.1, 0.15, and 0.2 mbar) drying, found that moisture content and water activity values of the samples dried using hot air increased with air temperature and were higher when compared to the values obtained with the microwave and freeze drying methods. According to the authors, crust formation on the product surface due to high drying temperatures acted as barrier to the removal of water from the product, consequently leading to higher water activity and moisture content values.…”
Section: Impact Of Processing Conditions and Product Characteristics On Drying Kineticsmentioning
confidence: 99%
“…The D eff of the beef jerky injected with 30% brine was the highest (p<0.05). The physical properties, such as volumetric heating, large evaporation, and structure, have a significant influence on the efficiency, energy consumption, and some quality parameters of the final product ( Elmas et al, 2020 ). The MC plays an important role in changing the pore network and D eff ( Chen, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…The above equation can be simplified by eliminating terms with negligible values as they do not significantly impact the drying of the samples (Elangovan & Natarajan, 2021;Elmas et al, 2020;Macedo, Vimercati, da Silva Araújo, Saraiva, & Teixeira, 2020). The above Equation ( 1) can be rewritten as:…”
Section: Moisture Diffusivity and Activation Energymentioning
confidence: 99%